Fabrication and thermal conductivity of highly porous alumina body from platelets with yeast fungi as a pore forming agent. Issue 12 (September 2016) - Honda, Sawao; Hashimoto, Shinobu; Yase, Shizuka; Daiko, Yusuke; Iwamoto, Yuji
Abstract: A highly porous alumina body was fabricated by heating a green clinker body consisting of platelets and yeast fungi as a pore forming agent. Four kinds of alumina platelets were used. When green clinker bodies of platelet aggregates (A11) with 10 and 30 mass% of yeast fungi were heated at 1500 °C for 2 h, their porosities reached 72% and 78%, respectively. In contrast, when the green clinker bodies composed of platelets with an average size of 10 µm and an aspect ratio of 25–30 (SERATH①), and 20 mass% of yeast fungi were heated at 1400 °C for 2 h, the porosity of the resultant porous alumina body was also approximately 72%. However, the room temperature thermal conductivities of the porous alumina bodies with 72% porosity derived from A11 and SERATH① were 0.86 and 0.50 W m −1  K −1, respectively. The decrease in the thermal conductivity of the porous alumina body produced from SERATH① is caused by the long path route for heat transfer.